2022
DOI: 10.1101/2022.02.18.481065
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparing the value of mono- versus coculture for high-throughput compound screening in hematological malignancies

Abstract: The bone marrow microenvironment modulates treatment response in blood cancers but a systematic assessment of anticancer drug effects in the context of this protective niche has been missing. To fill this gap, we established an ex-vivo model that enables high-throughput compound screening in leukemia-stroma coculture. We applied 50 compounds to 108 patient samples with hematological malignancies in monoculture and coculture with bone marrow stromal cells and measured cellular phenotypes via automated confocal … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 77 publications
(145 reference statements)
0
3
0
Order By: Relevance
“…Coculture tumor models have emerged as a diverse tool to interrogate interactions between multiple cell types, such as tumor and stromal cells. Cocultures have been used as a cell model to study heterotypic cell signaling and proteomic crosstalk in pancreatic, liver, and breast cancer, and they have recently started to be used to examine processes in CRC. Mammalian in vitro cocultures have shown decreased sensitivity to drug therapies compared to monocultures. However, most preclinical research uses monoculture models, which often fail to capture the cell heterogeneity found within in vivo tumors …”
Section: Discussionmentioning
confidence: 99%
“…Coculture tumor models have emerged as a diverse tool to interrogate interactions between multiple cell types, such as tumor and stromal cells. Cocultures have been used as a cell model to study heterotypic cell signaling and proteomic crosstalk in pancreatic, liver, and breast cancer, and they have recently started to be used to examine processes in CRC. Mammalian in vitro cocultures have shown decreased sensitivity to drug therapies compared to monocultures. However, most preclinical research uses monoculture models, which often fail to capture the cell heterogeneity found within in vivo tumors …”
Section: Discussionmentioning
confidence: 99%
“…The lack of primary CLL cell proliferation in vitro poses challenges to studying this process, which is fundamental for understanding disease progression and aggressiveness. Several in vitro microenvironment model systems have been developed to study CLL biology, perform in vitro screening of chemical libraries for compounds with anti-CLL activity, and guide therapeutic decisions [19][20][21][22]. Most such co-culture models involve human or murine fibroblast-like stromal cells that provide signals to overcome spontaneous CLL cell apoptosis and/or mimic adhesion-mediated drug resistance, but these do not trigger proliferation [4,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated individual components of the microenvironment in leukaemia (Dietrich et al , 2012 ; Chatzouli et al , 2014 ; Jayappa et al , 2017 ; Chen et al , 2019 ; preprint: Herbst et al , 2022a ). However, systematic studies, particularly those exploring cell‐extrinsic influences on drug response, are rare.…”
Section: Introductionmentioning
confidence: 99%